Spin-Vibronic Coupling Controls the Intersystem Crossing of Iodine-Substituted BODIPY Triplet Chromophores - Doležel, Jiří; Poryvai, Anna; Slanina, Tomáš; Filgas, Josef; Slavíček, Petr (Chemistry (Weinheim an der Bergstrasse, Germany), 2024)
4,4-Difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) dyes are extensively used in various applications of their triplet states, ranging from photoredox catalysis, through triplet sensitization to photodynamic therapy. However, the rational design of BODIPY triplet chromophores by ab initio modelling is limited by their strong interactions of spin, electronic and vibrational dynamics. In particular, spin-vibronic coupling is often overlooked when estimating intersystem crossing (ISC) rates. In this study, a combined experimental and theoretical approach using spin-vibronic coupling to correctly describe ISC in BODIPY dyes was developed. For this purpose, seven π-extended BODIPY derivatives with iodine atoms in different positions were examined. It was found that the heavy-atom effect of iodine atoms is site specific, causing high triplet yields in only some positions. This site-specific ISC was explained by El-Sayed rules, so both the contribution and character of the molecular orbitals involved in the excitation must be considered when predicting the ISC rates. Overall, the rational design of BODIPY triplet chromophores requires using (i) the high-quality electronic structure theory, including both static and dynamical correlations; and (ii) the two-component wave function Hamiltonian, and rationalizing; and (iii) ISC based on the character of the molecular orbitals of heavy atoms involved in the excitation, expanding El-Sayed rules beyond their traditional applications.
Keywords: intersystem crossing; El-Sayed rules; BODIPYs; triplet chromophores; spin-vibronic couplings